Southeast Kansas Regional Study - Howard, Ian; Shearmire, Brantlee (Kansas State University, The Chapman Center for Rural Studies, 2011)
The 1850's frontier amalgamation of different cultures and people helped create one of the most unheralded yet demographically and geographically diverse regions in American history, with traces of its existence still evident today.
Howard and Sheamire, “Southeast Kansas Regional Study,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/25.
Keywords: Miami County; Ottawa; Pottawatomie; Algonquian; Chippewa; Kaskaskia